Wilt of peanut caused by Fusarium solani (Mart.) Sacc - Lima, Débora Maria Massa; Aguillar, Juan Angel Espinal (Pesquisa Agropecuaria Brasileira, 2014)
The present paper is based on an experimental study of the peanut-wilt caused by Fusarium solani (Mart.) Sacc. which occurred in the Experimental Station of Itapirema, Pernambuco. This report constitutes the first record of this wilt in the state of Pernambuco. The fungus was isolated in potato-dextrose-agar from infected tissues and its pathogenicity was proved in the laboratory on peanut plants grown in vessels filled with sterilized soil. The inoculations were made in two ways: (i) by dipping the seed as well as five, ten and fifteen days old seedlings in the spores suspension, and (ii) by irrigating the soil in the vessel with the spores suspension. Pathogenetic period was approximately 26-30 days.